2004
DOI: 10.1074/jbc.m409188200
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-1/DEC2 Inhibits Skeletal Muscle Differentiation through Repression of Myogenic Transcription Factors

Abstract: Skeletal muscle differentiation is regulated by the basic-helix-loop-helix (bHLH) family of transcription factors. The myogenic bHLH factors form heterodimers with the ubiquitously expressed bHLH E-proteins and bind E-box (CANNTG) sites present in the promoters of several muscle-specific genes. Our previous studies have shown that the bHLH factor Sharp-1 is expressed in skeletal muscle and interacts with MyoD and E-proteins. However, its role in regulation of myogenic differentiation remains unknown. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 62 publications
4
89
0
Order By: Relevance
“…As an additional assay of apoptosis, we used an anti-PARP antibody (Cell Signaling Tech Inc., Danvers, MA, USA) by western blot in stable transfected cells; again, we found no evidence of PARP protein cleavage (not shown). Instead, quantitative PCR of NCI-H520 cells stably transfected to overexpress BHLHB3 (Figure 3) and using cyclin D1 as a marker of proliferation (Berthet and Kaldis, 2007) revealed a decrease (0.25 ± 0.04-fold, n ¼ 8) of cyclin D1 mRNA expression (measured using Hs00277039_m1 (CCND1) TaqMan Gene Expression Assays; Applied Biosystems, Foster City, CA, USA) in BHLHB3-transfected versus vector-transfected cells, consistent with western blot analysis ( Figure 3) and with a previous study (Azmi et al, 2004) showing that BHLHB3 overexpression in mouse myoblast cell line C2C12 promotes cell cycle exit in association with decreased levels of cyclin D1 protein expression. Indeed, inhibition of cyclin D1 protein expression is associated with cell cycle arrest in cancer cell lines (Berthet and Kaldis, 2007).…”
supporting
confidence: 88%
“…As an additional assay of apoptosis, we used an anti-PARP antibody (Cell Signaling Tech Inc., Danvers, MA, USA) by western blot in stable transfected cells; again, we found no evidence of PARP protein cleavage (not shown). Instead, quantitative PCR of NCI-H520 cells stably transfected to overexpress BHLHB3 (Figure 3) and using cyclin D1 as a marker of proliferation (Berthet and Kaldis, 2007) revealed a decrease (0.25 ± 0.04-fold, n ¼ 8) of cyclin D1 mRNA expression (measured using Hs00277039_m1 (CCND1) TaqMan Gene Expression Assays; Applied Biosystems, Foster City, CA, USA) in BHLHB3-transfected versus vector-transfected cells, consistent with western blot analysis ( Figure 3) and with a previous study (Azmi et al, 2004) showing that BHLHB3 overexpression in mouse myoblast cell line C2C12 promotes cell cycle exit in association with decreased levels of cyclin D1 protein expression. Indeed, inhibition of cyclin D1 protein expression is associated with cell cycle arrest in cancer cell lines (Berthet and Kaldis, 2007).…”
supporting
confidence: 88%
“…The Id proteins are HLH factors that lack the basic DNA-binding domain and competitively heterodimerize with E-proteins, preventing DNA binding to an E-box (Benezra et al 1990). In addition, Eproteins can heterodimerize with bHLH transcriptional repressors, such as HES proteins (Dec2) (Azmi et al 2004;Fujimoto et al 2007) or Twist (Kophengnavong et al 2000) or, as in this study, MSC (see also Lu et. al.…”
Section: Discussionmentioning
confidence: 61%
“…Although DEC1 prevents neither C/EBPβ nor RXR from binding to its target gene, DEC1 prevents bHLH domain containing transactivators such as BMAL1, MyoD and SREBP-1c, from binding to their target DNA by either protein-protein interaction or by directly binding to their responsive elements containing an E-box (Azmi et al, 2004;Choi et al, 2008;Li et al, 2004). Recently, Gulbagci et al demonstrated that DEC2, isoform of DEC1, also interacts with C/EBPβ and increases the recruitment of histone methyltransferase G9a to the promoter of PPARγ2 (Gulbagci et al, 2009).…”
Section: Dec1 Is Recruited On the Promoter Of Pparγ2mentioning
confidence: 99%